The Effect of AI-Based Sketch Metademolab Media on Second Grade Elementary Students’ Interest in Visual Arts Learning - Prima Samtiadji; Sigit Yulianto (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
Art education in elementary schools still faces challenges in improving students’ learning interest due to the use of conventional learning media that provide limited visual-interactive experiences. This study aimed to analyze the effect of Sketch Metademolab AI media on the art learning interest of second-grade elementary school students. The study employed a quasi-experimental method using a pretest-posttest control group design involving experimental and control groups. Data were collected using a learning interest questionnaire and analyzed through paired samples t-tests, independent samples t-tests, N-Gain analysis, and Cohen’s d effect size. The findings revealed that the average learning interest score of the experimental group increased from 72.67 to 76.86, while the control group decreased from 75.92 to 71.96. Statistical analysis indicated a significant difference between the two groups (p < 0.001). The N-Gain score of the experimental group was 0.61, categorized as moderate, while the control group obtained 0.35, categorized as low. Furthermore, Cohen’s d value of 1.054 was categorized as a large effect, indicating a strong influence of the media on improving students’ learning interest. These findings demonstrate that Sketch Metademolab AI media effectively enhances students’ interest in art learning through visual-interactive learning in elementary schools.